Basic Parameters of Drying Device with Inner Netted Receptacle - A. A. Askarova; O. Zh. Apbozov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents a selected method for drying high wet bulk products with uniform distribution of a drying product in inter-grain space of a compact fixed layer. In order to implement the selected drying method it is recommended to apply a device with inner receptacle having a channel  whose cross-section is decreasing along movement of a  thermal flow.   Specific feature of the accepted drying device design is that the process is carried out in continuous mode: temperature and  heated air velocity along the height and width of the drying chamber are unchangeable due to design of heat supply channel located inside of netted receptacle. An analytical expression has been derived in order to  calculate resistance to movement of thermal flow – heated air – in a compact fixed layer of product mass.